EVALUASI PROGRAM SANIMAS (SANITASI MASYARAKAT) MCK KOMUNAL DI KOTA KEDIRI DENGAN PENDEKATAN MULTIDIMENSIONAL SCALLING DAN TCR - Aulia Ulfah Farahdiba; Nita Galuh Apriliani (EnviroUS, 2022)
The city of Kediri is one of the cities that received assistance from the SANIMAS program. All facilities built are communal toilets. This study aims to evaluate 5 Communal MCK Sanimas in Kediri City through two aspects. The first is the usability aspect where the data is processed using TCR with respondents coming from the user community, and the second is the sustainability aspect, where the data is processed using MDS Rapsanimas with respondents coming from experts related to Communal MCK Sanimas. The results of this study are from the aspect of usefulness, it says that Dandangan 1 gets a very good score, and the last one Balowerti gets a bad score. While the results of the MDS Rapsanimas get the final results of Dandangan 1 and Dandangan 2 the level of sustainability is good, and Ngadirejo's level of sustainability is less.